The incidence of pelvic fractures and related surgery in the Finnish adult population: a nationwide study of 33,469 patients between 1997 and 2014 - Rinne, Pasi P; Laitinen, Minna K; Kannus, Pekka; Mattila, Ville M (Acta orthopaedica, 2020)
Background and purpose - Information on the epidemiological trends of pelvic fractures and fracture surgery in the general population is limited. We therefore determined the incidence of pelvic fractures in the Finnish adult population between 1997 and 2014 and assessed the incidence and trends of fracture surgery. Patients and methods - We used data from the Finnish National Discharge Register (NHDR) to calculate the incidence of pelvic fractures and fracture surgery. All patients 18 years of age or older were included in the study. The NHDR covers the whole Finnish population and gives information on health care services and the surgical procedures performed. Results and interpretation - We found that in Finnish adults the overall incidence of hospitalization for a pelvic fracture increased from 34 to 56/100,000 person-years between 1997 and 2014. This increase was most apparent for the low-energy fragility fractures of the elderly female population. The ageing of the population is likely therefore to partly explain this increase. The annual number and incidence of pelvic fracture surgery also rose between 1997 and 2014, from 118 (number) and 3.0 (incidence) in 1997 to 187 and 4.3 in 2014, respectively. The increasing number and incidence of pelvic fractures in the elderly population will increase the need for social and healthcare services. The main focus should be on fracture prevention.